Morphological abnormality in larvae of Amblyomma oblongoguttatum (Acari: Ixodidae) (Veterinária Notícias, 2019)
Amblyomma oblongoguttatum is a tick that is a parasite of mammals andits preferred hosts are the wild pigs, tapirs and small rodents, beingcollected also parasitizing domestic dogs and eventually humans. AnAmblyomma oblongoguttatum larva with morphological abnormality wascollected along with other specimens (larvae and females) of this speciesand with morphologically normal Amblyomma naponense nymphs in awild pig - Pecari tacaju - in a rural area of the state of Rondônia / Brazil,during research of tick-borne disease environments. The morphologicallyabnormal specimen showed a bifurcation of the posterior region of theopisthosoma, without other altered morphological characters. This is thefirst record of morphological abnormality at the larval stage ofAmblyomma oblongoguttatum.